RECENT APPROACHES OF SOLID DISPERSION: A NEW CONCEPT TOWARD ORAL BIOAVAILABILITY . - Bindhani, Sabitri; Mohapatra, Snehamayee (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Solid dispersion (SD) has been a major advanced technology in overcoming dissolution and bioavailability problem of poorly soluble compounds. Formulation of SD in water-soluble carrier has becoming more researched over the past four decades for solubility and relative bioavailability enhancement. By reduction of the size of the drug particle to the minimum level which will enhance drug wettability and ultimately bioavailability will be definitely improved. This review article elaborates recent advanced technology and characterization of SDs and also discusses the problems and their solution for the development of better formulations.